The Process of Self-Cultivation and the Mandala Model of the Self - Wu, Meiyao (Frontiers in Psychology, 2017)
In his Mandala model of the self, Taiwanese scholar Kwang-Kuo Hwang sees each human being as a combination or intersection of private individual and social person, and also of knowledge and action. To further elaborate the model—with a particular emphasis on teaching/learning, the development of the ideal self and spiritual transcendence—this article will explore the psychological process of self-cultivation in the light of traditional Confucian thinking, which means keeping a balance between inner/outer and self/other. The Neo-Confucian thinker Zhongsha Mou’s theories of “the awareness of unexpected developments” and his meditation/ cognitive thinking opposition will also be discussed. The analyzed sources will include the traditional Confucian classics (the Four Books and Liji, or Classic of Rites) and especially the “Lessons for Learning (Xue-Ji)” in the Classic of Rites (Liji), along with the relevant textual research. Based upon a cultural-semantic analysis of these classics as well as of Hwang’s central ideas, the author attempts to further conceptualize the process of cultivating the ideal self in Confucian education.